2014
DOI: 10.1002/mds.26110
|View full text |Cite
|
Sign up to set email alerts
|

Progression of gait dysfunction in incident Parkinson's disease: Impact of medication and phenotype

Abstract: Gait impairment in Parkinson's disease (PD) persists despite the use of dopaminergic therapy. Motor phenotype associated with greater postural instability and gait difficulty is related to a greater risk of motor decline and may be influenced by non-dopaminergic pathology. This study documents the progression of gait impairment over 18 months in an incident cohort of PD with regard to phenotype and medication. Gait characteristics were measured in 121 PD and 184 controls, and 18 months later in 108 PD particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
174
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 177 publications
(194 citation statements)
references
References 45 publications
15
174
5
Order By: Relevance
“…22 Gait was quantified according to an a priori model developed for older adults 23 and validated in PD 24 that describes 16 discrete gait characteristics. 25 We examined change in each gait characteristic over 36 months and characteristics that exhibited substantial change (despite optimal medication) were defined as doparesistant. Quantification of CSF biomarkers.…”
mentioning
confidence: 99%
“…22 Gait was quantified according to an a priori model developed for older adults 23 and validated in PD 24 that describes 16 discrete gait characteristics. 25 We examined change in each gait characteristic over 36 months and characteristics that exhibited substantial change (despite optimal medication) were defined as doparesistant. Quantification of CSF biomarkers.…”
mentioning
confidence: 99%
“…27,28 PIGD subtype is also associated with faster gait deterioration 30 and increased fall frequency. 26,31 It appeared that most individuals with PIGD in our study were already in the high fall risk trajectory.…”
Section: Discussionmentioning
confidence: 98%
“…The addition of a gyroscope sensor within the BWM would allow the complete quantification of the 16 gait characteristics identified as important [27,28]. Additionally, the extra sensor would allow the correct identification and allocation of left/right steps.…”
Section: Study Limitations and Future Workmentioning
confidence: 99%
“…Whilst multiple characteristics can describe gait, studies have helped to provide a simplified framework for selection of important gait characteristics [5,26,27]. In this study characteristics were selected based on our previous work [27,28] which identified a comprehensive range of 16 core gait characteristics (using GaitRite) recognised as indicative of healthy ageing and pathology (Parkinson's disease, PD). Here, we used a BWM and adopted a novel combination of two algorithms to quantify gait grouped by the properties they measure such as summary mean values, variability and asymmetry and including phases of the gait cycle.…”
mentioning
confidence: 99%